Abrumados por las hipotecas - Palomo Garrido, Aleksandro (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
A chill crosses the financial body´s backbone anywhere in the world. The hypothecating crisis worsens and still it will have to spend time until touching bottom. The prices of the house are falling as it were not seen from the years of the great depression of 1929 and the explosion of the housing bubble is united to the credit´s one that is splashing to the great banks.